Differential Regulation of Human Surfactant Protein A Genes, SFTPA1 and SFTPA2, and Their Corresponding Variants - Floros, Joanna; Tsotakos, Nikolaos (Frontiers in Immunology, 2021)
The human SFTPA1 and SFTPA2 genes encode the surfactant protein A1 (SP-A1) and SP-A2, respectively, and they have been identified with significant genetic and epigenetic variability including sequence, deletion/insertions, and splice variants. The surfactant proteins, SP-A1 and SP-A2, and their corresponding variants play important roles in several processes of innate immunity as well in surfactant-related functions as reviewed elsewhere (Floros et al., 2021). The levels of SP-A have been shown to differ among individuals both under baseline conditions and in response to various agents or disease states. Moreover, a number of agents have been shown to differentially regulate SP-A1 and SP-A2 expression. The focus in this review is on the differential regulation of SP-A1 and SP-A2 with primary focus on the role of 5’ and 3’ untranslated regions (UTRs) and flanking sequences on this differential regulation as well molecules that may mediate the differential regulation.